Social calls honestly signal female competitive ability in Asian particoloured bats. (May 2017) - Luo, Bo; Lu, Guanjun; Chen, Kelly; Guo, Dongge; Huang, Xiaobin; Liu, Ying; Feng, Jiang
Abstract : Why a variety of social animals vocalize during agonistic foraging interactions remains obscure. One possibility is that these signals advertise the signaller's competitive ability, playing a role in the defence of food resources, yet there is limited evidence in support of this idea. Here, we used adult female Asian particoloured bats, Vespertilio sinensis, to test whether individual variation in competitive ability when foraging can be explained by social calls. Using synchronized infrared video and audio recording, we monitored bat social vocalizations, dominance rank and weight gain in triads under controlled food conditions. Additionally, subsequent playbacks, consisting of experimental stimuli, echolocation pulses and silence, were presented to feeding bats in a laboratory. Analyses showed that females uttered low-frequency social calls composed of one to five syllable types during feeding competition. The rates of social vocalizations increased with reduced food availability. Interestingly, dominance score and weight gain correlated weakly with body size, but positively with call rate and associated parameters. Playback of social calls inhibited the visits of bats to the focal food dish compared to playback of silence and echolocation pulses. The amount of food consumed was greatly reduced in the presence of experimental stimuli versus controls. Collectively, these results highlight that acoustic signals serve as an honest indicator of bat competitive ability. Highlights: We tested the relationship between vocalizations and competitive ability in bats. Bats uttered more social calls when food availability decreased. Rates of social vocalizations predicted female dominance status. Rates of social vocalizations predicted female weight change. Social calls given by females serve a food defence function.